Integration of metabolomic and transcriptomic analyses reveals regulatory functions of the ChREBP transcription factor in energy metabolism - Jie An; Inna Astapova; Guofang Zhang; Andrew L. Cangelosi; Olga Ilkayeva; Hannah Marchuk; Michael J. Muehlbauer; Tabitha George; Joseph Brozinick; Mark A. Herman; Christopher B. Newgard (Cell Reports)
Summary: The transcription factor carbohydrate response element binding protein (ChREBP) activates genes of glucose, fructose, and lipid metabolism in response to carbohydrate feeding. Integrated transcriptomic and metabolomic analyses in rats with GalNac-siRNA-mediated suppression of ChREBP expression in liver reveal other ChREBP functions. GalNac-siChREBP treatment reduces expression of genes involved in coenzyme A (CoA) biosynthesis, with lowering of CoA and short-chain acyl-CoA levels. Despite suppression of pyruvate kinase, pyruvate levels are maintained, possibly via increased expression of pyruvate and amino acid transporters. In addition, expression of multiple anaplerotic enzymes is decreased by GalNac-siChREBP treatment, affecting TCA cycle intermediates. Finally, GalNAc-siChREBP treatment suppresses late steps in purine and NAD synthesis, with increases in precursors and lowering of end products in both pathways. In sum, our study reveals functions of ChREBP beyond its canonical roles in carbohydrate and lipid metabolism to include regulation of substrate transport, mitochondrial function, and energy balance.